CODE SWITCHING USED BY INDONESIAN IDOL 2012 COMMENTATOR IN SPECTACULAR CONCERTS OF INDONESIAN IDOL 2012 ON RCTI - JEFFREYAWAN, JENITRA (Jurnal Ilmiah Mahasiswa FIB, 2013)
In communication, people often use more than one code. In this case people may switch from one code to another code for certain purpose. This kind of phenomenon is called as Code Switching. Code switching is a linguistics term that basically means switching back and forth between two or more languages in the course of a conversation. A study on code switching from one variety of language to another variety of the same language is interesting to be discussed since it can reflect social, cultural, and individual preference. This study examines code switching used in Indonesian idol TV program which is focused on the code switching used by Agnes Monica as one of the commentators in that program. The purposes of this study are to figure out: (1 ) Types of code switching utterances used by commentator in spectacular concerts of Indonesian Idol 2012 on RCTI. (2) Factors that influence the use of code switching by commentator in spectacular concerts of Indonesian Idol 2012 on RCTI. The research design applied in this study is descriptive-qualitative. The data in this study are the utterances of Agnes Monica, one of the commentators in Indonesia Idol 2012. These utterances were recorded when she was giving the comment and evaluating the performance on the stage after singing. In this way, the researcher analyzed Indonesian Idol spectacular show episode 1. The results of this research show that Agnes switches the code when giving the comment to the contestants after singing. Agnes switches the code from Bahasa Indonesia to English, English to Bahasa Indonesia, Bahasa Indonesia to local language (Betawi), and local language (Betawi) to English. There are two kinds of code switching used by Agnes. They are internal code switching, and external code switching. The mostly used type of code switching by Agnes is external code switching. There are dominant factors namely participant and setting that influence the use of code switching. The researcher suggests that  this reserach hopefully can be used for teaching material. Also the researcher suggests to the next researchers who are going to do an analysis about code switching uses different theory and different data. . Key Words: Code Switching, Agnes Monica.